2012
DOI: 10.1002/cne.22742
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide F immunoreactive clock neurons modify evening locomotor activity and free‐running period in Drosophila melanogaster

Abstract: Different subsets of Drosophila melanogaster's clock neurons are characterized by their specific functions in daily locomotor rhythms and the differences in their neurotransmitter composition. We investigated the function of the neuropeptide F (NPF) immunoreactive clock neurons in the rhythmic locomotor behavior of adult flies. We newly identified the fifth s-LN(v) and a subset of the l-LN(v)s as NPF-positive in addition to the three LN(d)s that have been described previously. We then selectively ablated diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
100
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 41 publications
(93 reference statements)
4
100
0
Order By: Relevance
“…Locomotor activity of individual flies was recorded using the Drosophila Activity Monitoring (DAM) System (Trikinetics) as previously described [67]. Briefly, to investigate locomotor behavior 3–7 day old male flies were monitored in LD 12∶12 for 7 days (with a light intensity of 100 lux in the light phase) followed by additional 14 days in constant darkness (DD).…”
Section: Methodsmentioning
confidence: 99%
“…Locomotor activity of individual flies was recorded using the Drosophila Activity Monitoring (DAM) System (Trikinetics) as previously described [67]. Briefly, to investigate locomotor behavior 3–7 day old male flies were monitored in LD 12∶12 for 7 days (with a light intensity of 100 lux in the light phase) followed by additional 14 days in constant darkness (DD).…”
Section: Methodsmentioning
confidence: 99%
“…However, in R. pedestris, the circadian clock has been shown to be involved in the photoperiodic response (Ikeno et al, 2010;Ikeno et al, 2011a;Ikeno et al, 2011b;Ikeno et al, 2011c;Ikeno et al, 2013), suggesting that these neurons would also be the circadian clock neurons. Such PDFimmunonegative circadian clock neurons are indeed observed in D. melanogaster (Rieger et al, 2006;Picot et al, 2007;Hermann et al, 2012). To interpret the effects of Site 1 removal at a cellular level, a neuroanatomical study of this region will be necessary.…”
Section: Research Articlementioning
confidence: 98%
“…Neuropeptide F (NPF) and its receptor NPFR1, help regulate evening anticipation. NPF is produced in two to three l-LNvs, three LNds, and the fifth s-LNv (Hermann et al 2012;Kim et al 2013), with one study reporting production in all four s-LNvs (He et al 2013), although not consistently observed by others (Fig. 1D) (Hermann et al 2012;Kim et al 2013).…”
Section: Other Neuropeptides and Evening Anticipationmentioning
confidence: 80%
“…NPF is produced in two to three l-LNvs, three LNds, and the fifth s-LNv (Hermann et al 2012;Kim et al 2013), with one study reporting production in all four s-LNvs (He et al 2013), although not consistently observed by others (Fig. 1D) (Hermann et al 2012;Kim et al 2013). The s-LNvs do express NPFR1 however, which associates with Gi to inhibit cAMP production (Garczynski et al 2002;Kim et al 2013) that may antagonize PDFR or D1-like DA receptor production of cAMP in these neurons (Fig.…”
Section: Other Neuropeptides and Evening Anticipationmentioning
confidence: 81%
See 1 more Smart Citation